Chapter 6 Time to entry and business tourism: panel duration models with censored data (2019)
The rates at which new organizations are created and at which organizations disappear or grow are of obvious interest. Managers or investors both want to know what puts economic agent at risk of failure, or conversely, helps them to register a new firm. Length of time in starting entrepreneurship project is one of the most important factors in decisions made by entrepreneur as it conditions their initial expenditure, and may cause psychological stress if opening is long-lasting. Developing countries are often characterized by burdensome regulations, which are perceived as an important obstacle to firm creation, formalization and growth. In order to reduce this regulatory burden, many countries have devoted substantial efforts to reduce the monetary and non-monetary costs of registering a business [Bruhn and McKenzie (2014)]. Kaplan et all (2011) estimate the effect on business start-ups of a program that significantly speeds up firm registration procedures. The following research questions are asked in this paper in an effort to analyze the main problem: what determinants explain and predict the probability that a some country in Europe and its average entrepreneur in it would spend shorter time in activities which elapse between starting and finishing constitution of a new firm, and what significant determinants divides the countries groups based on their similarity.